Actively tuning of transverse wave band gaps in hybrid sandwich beam metamaterials with shunted piezoelectric array and inertial amplification mechanism. (December 2022) - Li, Jingru; Yang, Peng; Xia, Maolong
In this paper, a tunable sandwich beam metamaterial is designed by implementing a hybrid project composed of the piezoelectric shunted array technique and the inertial amplification mechanism. Concerned with the shunted piezoelectric constitutive relation, the kinematic analysis of added mechanism and the transverse motion of base structure, a theoretical model is established to estimate the band gap characteristics of the sandwich beam lined with pyramidal truss cores using the transfer matrix method, whose accuracy is further validated by the finite element simulations. Numerical results show that multiple stop bands are generated at low frequencies owing to the mechanisms of electromechanical resonance, amplifying inertia and mechanical resonance, certainly enhancing the level of vibration suppression. Subsequently, a comprehensive parametric analysis is conducted to investigate the influences of the shunting circuits and attached mechanism on the attenuation diagrams. It is demonstrated that the hybrid sandwich lattice can offer more tunable space to acquire ultra-broad band gaps. Furthermore, based on the design potential, the amplitudes and bandwidths of the attenuation region are maximized by operating an optimization study. Such advanced attenuation performance can be applied for a wide range of engineering applications.